The End of The Road - Sean Hermanson (European Journal of American Studies)
The closing paragraph of Cormac McCarthy’s The Road hums with mystery. Some find it suggestive of renewal, though only vaguely. Others contend that it does little to ameliorate the novel’s pessimism. Still others find it offers both lamentation and hopefulness, while some pass it over in silence. As an admirer with a taste for puzzle solving, here I offer a new interpretation revealing a surprisingly optimistic denouement.